Teacher Professional Development Planning at SMAN 6 Palembang - Amilda; Jumhur (Didaktika: Jurnal Kependidikan, 2024)
This study delves into the topic of professional development planning for teachers at SMAN 6 Palembang. Program sustainability planning, activity planning, time planning, and financial planning are the intended topics of this research. In order to address the research question—how to organize teacher professional development in terms of activity, time, money, and program sustainability—this study used a qualitative method. Interviews, observations, and documentation studies are the methods used to gather data. Methods of purposive sampling are used in the selection of informants. Utilizing triangulation and member verification procedures, the reliability of the data is verified. Data analysis consists of four steps: gathering data, presenting it, checking it, and drawing conclusions. Results and discussion indicated that using teacher development patterns in activity planning is similar to adopting top-down policy rather than focusing on teachers' actual requirements in terms of professional development. Planning for teachers' professional development time has not been owned by schools, the Education Office, or teachers themselves. The majority of our growth time is dictated by external factors and the level of personal motivation from our teachers when it comes to self-improvement. Planning for the Teacher-Experienced Development Fund is not entirely the responsibility of teachers. Despite many school requirements, the needs of instructors are not taken into account when budgeting funds. School budgets have to go somewhere, and no one has thought about the long-term or short-term viability of teacher professional development programs while they were planning their sustainability.